2019
DOI: 10.1038/s41467-019-09411-7
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule end conversion mediated by motors and diffusing proteins with no intrinsic microtubule end-binding activity

Abstract: Accurate chromosome segregation relies on microtubule end conversion, the ill-understood ability of kinetochores to transit from lateral microtubule attachment to durable association with dynamic microtubule plus-ends. The molecular requirements for this conversion and the underlying biophysical mechanisms are elusive. We reconstituted end conversion in vitro using two kinetochore components: the plus end–directed kinesin CENP-E and microtubule-binding Ndc80 complex, combined on the surface of a microbead. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 64 publications
8
55
0
Order By: Relevance
“…Upon entry into M-phase (mitosis or meiosis) and spindle assembly, chromosomes are often initially transported to the spindle poles, where the microtubule density is highest, and from there to the spindle’s equatorial plane, forming lateral attachments to the microtubule lattice. CENP-E, a kinetochore-localized, microtubule-plus-end-directed motor plays an essential function in this process (Bancroft et al, 2015; Barisic et al, 2014; Cai et al, 2009; Chakraborty et al, 2019; Kapoor et al, 2006; Kim et al, 2008; Kitajima et al, 2011; Magidson et al, 2011; Shrestha et al, 2017; Tanaka et al, 2005). In a poorly understood process of ‘end-conversion’, kinetochores engage the microtubule-binding interface of the KMN network and transition from binding to the lattice to binding to the dynamic plus ends of the microtubules, which become embedded into the kinetochore’s outer plate (Dong et al, 2007; Kuhn and Dumont, 2017; McIntosh et al, 2013; Wan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Upon entry into M-phase (mitosis or meiosis) and spindle assembly, chromosomes are often initially transported to the spindle poles, where the microtubule density is highest, and from there to the spindle’s equatorial plane, forming lateral attachments to the microtubule lattice. CENP-E, a kinetochore-localized, microtubule-plus-end-directed motor plays an essential function in this process (Bancroft et al, 2015; Barisic et al, 2014; Cai et al, 2009; Chakraborty et al, 2019; Kapoor et al, 2006; Kim et al, 2008; Kitajima et al, 2011; Magidson et al, 2011; Shrestha et al, 2017; Tanaka et al, 2005). In a poorly understood process of ‘end-conversion’, kinetochores engage the microtubule-binding interface of the KMN network and transition from binding to the lattice to binding to the dynamic plus ends of the microtubules, which become embedded into the kinetochore’s outer plate (Dong et al, 2007; Kuhn and Dumont, 2017; McIntosh et al, 2013; Wan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Upon entry into M-phase (mitosis or meiosis) and spindle assembly, chromosomes are initially transported to the spindle poles, where the microtubule density is highest, and from there to the spindle's equatorial plane, forming lateral attachments to the microtubule lattice. CENP-E, a kinetochore-localized, microtubule-plus-end-directed motor plays an essential function in this process (Bancroft et al, 2015;Barisic et al, 2014;Cai et al, 2009;Chakraborty et al, 2019;Kapoor et al, 2006;Kim et al, 2008;Kitajima et al, 2011;Magidson et al, 2011;Shrestha et al, 2017;Tanaka et al, 2005). In a poorly understood process of "endconversion", kinetochores engage the microtubule-binding interface of the KMN network and transition from binding to the lattice to binding to the dynamic plus ends of the microtubules, which become embedded into the kinetochore's outer plate (Dong et al, 2007;Kuhn and Dumont, 2017;McIntosh et al, 2013;Wan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the unique capacity of human CLASPs to bind to curved microtubule protofilaments (Leano et al, 2013; Maki et al, 2015) and recent electron microscopy work showing that both growing and shrinking microtubule plus ends, including those of kinetochore microtubules, are curved (McIntosh et al, 2018). They are also supported by recent in vitro reconstitution experiments that showed that CLASP2-coated spherical beads are able to mediate moderately long-lived attachments with polymerizing microtubule plus-ends (Chakraborty et al, 2019). Unlike other TOG-domain containing proteins, such as members of the XMAP215/ch-TOG family that work as microtubule polymerases that bind to free α,β-tubulin heterodimers (Ayaz et al, 2012; Geyer et al, 2018; Nithianantham et al, 2018), our data is most consistent with a model in which microtubule lattice binding and EB protein-dependent microtubule plus-end tracking of CLASP2 is required at the kinetochore to stabilize, or prevent destabilization, of kinetochore-microtubule attachments as cells progress into metaphase.…”
Section: Resultsmentioning
confidence: 63%